Extração e caracterização da composição lipídica da borra de café e o estudo do potencial aproveitamento deste resíduo - Moura, Cleber Luiz de (2016)
The coffee grounds generated in large quantities in the production of instant coffee, has become a problem because it is an industrial waste. For the present a lipid content of about 20%, is the extraction of this oil for varied purposes. This study aimed to extract and characterize the lipid fraction of Robusta coffee grounds and Arabica for two extraction processes: extraction Soxtec as solvent petroleum ether, and pressurized by using ethanol as a solvent. It carried out the transesterification of oils from the coffee grounds through acidic and basic, for further characterization of the lipid profile of the oil sludge using gas chromatography-mass spectrometry (GC- MS). The hot extraction yields were on average 19.18% and 22.16% for Robusta and Arabica quality, respectively, whereas the yield obtained by the pressure was 18.1% Robusta quality. The transesterification via acid catalysis was more efficient in conversion of triagliceróis esters, as in base catalysis favors a saponification reaction because high free fatty acids content. The majority were identified as methyl palmitate around 30% Methyl linoleate and around 40% in about two species.